ToT and HRD competencies and its relationship to extension agents’ performance among cocoa smallholders - Motolani, MohdMustafaMunim; Hassan, Salim; Oluwatoyin, Olagunju; Kasin, Ramle (International Organization of Scientific Research, 2017)
The contribution of extension agents' (EA) competencies are considered crucial in transferring technology to the farmers. The study identify competency level of Extension Agents' on transfer of technology (ToT) and human resource development (HRD) to productive cocoa farmers (PCFs) in West Malaysia. The study employed stratified random sampling technique. A total of 353 PCFs were sampled to evaluate the competencies of the Extension agents' through the use of structured questionnaires to elicit response from the farmers. The data were analyzed using descriptive statistics and Pearson correlation analysis. The findings support the positive relationship between transfer of technology and work performance and also between human resource development and Extension agents' work performance. Finding revealed that required skills are needed in transfer of technology (ToT) as well as human resource development (HRD) to the farmers; this will play an important role in work performance of the extension agents' and also enhance their performance achievement which will increase cocoa smallholder potential for higher farm productivity.